MMP14 as a central mediator of TGF-β1−induced extracellular matrix remodeling in graves’ orbitopathy - Wang, Xing; Lu, Jing; He, Yuxia; Shu, Qinxin; Lin, Yuxin; Su, Wenqi; Wang, Peng (Frontiers in Endocrinology, 2025)
BackgroundGraves’ orbitopathy (GO) is an autoimmune orbital disorder characterized by chronic inflammation and aberrant extracellular matrix (ECM) remodeling, leading to progressive fibrosis. Recent studies implicate matrix metalloproteinase−14 (MMP14) in ECM degradation and tissue remodeling, yet its precise role in GO remains unclear.Design and methodsOrbital adipose/connective tissues specimens were obtained from GO patients (stratified into type I and type II based on clinical classification) and non−GO controls. High−throughput RNA sequencing identified differentially expressed genes, focusing on MMP−related transcripts. MMP14 expression was quantified by immunohistochemistry and Western blotting, correlating its levels with fibrotic grade. Primary orbital fibroblasts (OFs) isolated from GO and control subjects were cultured and stimulated with TGF−β1. Quantitative real−time PCR and Western blot assays evaluated MMP14 and fibroblast activation markers (α−SMA, COL1A1, CTGF). Transcriptomic profiling of TGF−β1–treated OFs and a scratch wound assay further assessed the effect of the MMP14 inhibitor NSC−405020 on cellular motility.ResultsGO type II tissues demonstrated a significant upregulation of MMP14, which correlated positively with fibrosis severity. GO− derived OFs exhibited higher basal and TGF−β1–induced MMP14 and fibrotic marker expression compared to controls. Transcriptomic analysis revealed activation of ECM–receptor interaction, PI3K−Akt, and MAPK signaling pathways enriched for MMP−associated genes. Pharmacologic inhibition of MMP14 attenuated TGF−β1–induced fibrotic markers and reduced OFs migration.ConclusionThese findings indicate that MMP14 is a central mediator in GO fibrotic remodeling, highlighting its potential as a therapeutic target to alleviate orbital fibrosis. Further mechanistic studies are needed to clarify MMP14’s role in GO progression.